Consolidation of W–Ta composites: hot isostatic pressing and spark and pulse plasma sintering - Dias, Marta (2016)
Composites consisting of tantalum fiber/powder dispersed in a nanostructured W matrix have been consolidated by spark and pulse plasma sintering as well as by hot isostatic pressing. The microstructural observations revealed that the tungsten–tantalum fiber composites consolidated by hot isostatic pressing and pulse plasma sintering presented a continuous layer of Ta2O5 phase at the W/Ta interfaces, while the samples consolidated by spark plasma sintering evidenced a Ta + Ta2O5 eutectic mixture due to the higher temperature of this consolidation process. Similar results have been obtained for the tungsten–tantalum powder composites. A (W, Ta) solid solution was detected around the prior nanostructured W particles in tungsten–tantalum powder composites consolidated by spark and pulse plasma sintering. Higher densifications were obtained for composites consolidated by hot isostatic pressing and pulse plasma sintering.